ДВОКОНТУРНИЙ РЕЗОНАНСНИЙ ПІДСИЛЮВАЧ ПОТУЖНОСТІ ДЛЯ МАГНІТНО-ІМПУЛЬСНОЇ ОБРОБКИ МЕТАЛІВ - Батигін, Ю.В.; Шиндерук, С.О.; Чаплигін, Е.О.; Фендриков, Д.В. (Інститут електродинаміки НАН України, Київ, 2022)
The authors propose and substantiate the functionality of a magnetic-pulse installation consisting of two blocks, the first of which is a resonant double-circuit charger of a capacitive energy storage, and the second block is a discharge circuit with an inductor-tool for performing a given production operation. It is shown that the voltage changes in time according to an exponentially growing harmonic law. It was found that the amplitude of the voltage across the capacitor can be regulated by varying the characteristics of the coupling transformer between the circuits and the characteristics of the circuit of the reactive power conversion unit. Numerical assessments of the characteristics of the charging process showed a high efficiency of voltage formation on the capacitive storage due to resonance phenomena (the transformation ratio is equal to the Q-factor of the circuit ~ 20), which is not comparable with the well-known traditional indicators of induction methods.  In terms of phase – the length in time to the maximum charge in the adopted circuit of the active electric power amplifier is set by the inequality - That is, after ~ 30 periods of charging current, the excited voltage reaches a maximum (~ 20 times higher than the source voltage), which will correspond to the end of the transient process and the establishment of a steady state of operation. An example of calculating the characteristics of an elementary resonant base illustrates the effective capabilities of a magnetic-pulse installation, consisting of a resonant charger of a capacitive energy storage and a load in the form of an inductor-tool for flat stamping of metal products. It was found that the square of the ratio of operating frequencies in the load unit and the reactive power amplification unit quantitatively determines the fundamental possibility of resonant amplification of the active electrical energy of a harmonic signal. References 12, figures 5.